Program Mitigasi Bagi Anak Terpapar HIV/AIDS - Nugroho, Fentiny (Jurnal Ilmu Kesejahteraan Sosial, 2008)
Mitigation services for children living with HIV/ AIDS who have done such as health and psychosocial services for children and also training and financial assistance for economic improvement for the child's parent Especially psychosocial services for children, not all agencies provide this service, so it's a service aspect that still needs to be developed. Mitigation model that has been done in general is family-based care, while community-based have limitations because there still exists the stigma from society. In implementation, the mitigation program experienced a number of obstacles, besides there is also a supporting factor